The CEE housing markets before, during and after the transition: An overview of property prices and home ownership rates - Elena Ionascu (CES Working Papers, 2017)
The purpose of this research is to investigate relevant economic aspects, which characterized housing markets from Central and Eastern European (CEE) countries, to identify the factors which determine the house prices and to find the economic implications of property investments, under an international micro and macroeconomic environment. Methodological, the article uses the deduction and comparative analysis of collected statistical data, and strategic reforms in post-communist countries are qualitatively explored through content analysis. In the case of CEE region, fundamentals determinants, such as real income, real interest rate, demographic factors, play an extremely important role in explaining house price distortions. The principles of communist ideology added a special note in the evolution of prices, so the home ownership rate, the housing quality, the financial housing system, European integration represent a number of traditional factors with significant impact.
Keywords: 330; CEE countries; housing prices; home ownership; privatization